IMPLEMENTATION OF THE PLAVON PROGRAM IN POPULATION ADMINISTRATION SERVICES IN SINGKALAN VILLAGE - Apriliana, Serly; Sukmana, Hendra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine the implementation of the Plavon program in population administration services in Singkalan Village. Method: Qualitative descriptive method with data collection techniques in the form of interviews, observations, and documentation studies. The informants in this study consist of village heads, Plavon operators, and villagers who are directly involved in the implementation of the program. Results: The results of this study show that the implementation of the PLAVON program in Singkalan Village is supported by adequate technological infrastructure and competent operators. However, there are still several obstacles, such as uneven socialization to all residents, limited understanding of the elderly community towards technology, and the support of the village head that has not been maximized. On the other hand, communication between implementers and coordination with the Dispendukcapil has gone well, the disposition of the implementers shows high commitment, and the bureaucracy has followed the applicable SOPs. Novelty: This research presents a novelty by applying Edward III's theory in the context of digital administrative services in Singkalan Village, which has never been researched before. Although such theories have been used in other studies, the focus on specific challenges such as limited public understanding and technical challenges in the implementation of the Plavon Program makes a new contribution. These findings enrich the study of e-Government at the local level and provide input for more inclusive digital service policies.